Analisis Pengaruh Kepercayaan dan Resiko Konsumen terhadap Niat Berbelanja di Forum Jual Beli (FJB) Kaskus menggunakan Technology Acceptance Model - Sepdiyah Ayu Ningrum; Ari Kusyanti; Himawat Aryadita (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-commerce is a bussiness transaction on the internet. One of famous e-commerce is Forum Jual Beli Kaskus (Trading Forum) at www.kaskus.co.id. Trustworthiness has always been an important element in influencing consumer behavior and in uncertain environtments, such as e-commerce. With so many fraud cases in e-commerce, there are a lot of hesistance of consumers because they are afraid of high risk to shopping in e-commerce. This research uses modification model of Technology Acceptance Model and data analysis by multiple linear regression. This research analyzes what variables affect the trust of the consumers and the risks of shopping on Kaskus. This research develops a theoretical framework that explains what affects trust and risk to one's intention to purchase on Kaskus. Data samples were collected through questionnaire-based surveys. The results show the familiarity with the website, consumer dispositions to trust, perceived privacy protection, perceived security protection, information quality from websites and positive reputation affect on consumer trust. Familiar with website, information quality and positive reputation does not affect the risk of purchasing in Kaskus. Consumer trust, risk, perceived usefulness and perceived ease of using the website affect a consumers to intention to purchase on Kaskus.